2019
DOI: 10.1029/2019gl084648
|View full text |Cite
|
Sign up to set email alerts
|

Central Asian Drying at 3.3 Ma Linked to Tropical Forcing?

Abstract: The processes controlling middle‐latitude environmental changes are poorly understood. Both high‐latitude ice sheets and tropical oceans can affect climate and environments in middle latitudes, but separating their relative contribution is challenging. Coincidence of intensive Northern Hemisphere glaciations and increased dust accumulation rates at ~2.7 Ma on the Chinese Loess Plateau and North Pacific Ocean is often used to indicate high latitudes' dominant role on middle‐latitude climate change. Here we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…These out‐of‐the‐order grain size coarsening events within interglacials correspond well with insolation maxima paced by orbital eccentricity (arrows in Figures 6h and 6j), an observation that is supported by recent studies that infer an increased imprint of eccentricity, and in association precession, in the Qaidam Basin under high eccentricity amplitudes (Luo et al, 2018; Su et al, 2019; Su et al, 2019). During eccentricity maxima the amplitude of precession is larger, causing a summer season lengthening and thus potentially enhanced EASM precipitation (Berger, 1988; Braconnot et al, 2008).…”
Section: Resultssupporting
confidence: 83%
“…These out‐of‐the‐order grain size coarsening events within interglacials correspond well with insolation maxima paced by orbital eccentricity (arrows in Figures 6h and 6j), an observation that is supported by recent studies that infer an increased imprint of eccentricity, and in association precession, in the Qaidam Basin under high eccentricity amplitudes (Luo et al, 2018; Su et al, 2019; Su et al, 2019). During eccentricity maxima the amplitude of precession is larger, causing a summer season lengthening and thus potentially enhanced EASM precipitation (Berger, 1988; Braconnot et al, 2008).…”
Section: Resultssupporting
confidence: 83%
“…Recently, magnetic parameters, including frequency‐dependent susceptibility (χ fd ) and χ fd /HIRM (χ fd to hard isothermal remanence magnetization ratio) have been demonstrated to faithfully track precipitation in the Loess Plateau and Qaidam Basin (Nie et al, 2017, 2020; Y. Song et al, 2014; Su et al, 2019). χ fd can detect the content of nm‐scale superparamagnetic (SP) ferrimagnetic grains of pedogenic origin and has been calibrated to precipitation using modern soils on the Chinese Loess Plateau (Maher & Thompson, 1995; Nie et al, 2010; Y.…”
Section: Discussionmentioning
confidence: 99%
“…Normalizing SP ferrimagnetic mineral content to hematite content therefore highlights the precipitation signal. χ fd /HIRM was initially calibrated using soils on the Chinese Loess Plateau (Z. F. Liu et al, 2013; Nie et al, 2017) but has shown great potential in fluvio‐lacustrine sediments without magnetic mineral dissolution (such as the Qaidam Basin strata) (Nie et al, 2017; Su et al, 2019). This is likely because the source regions have weathering crusts or soils recording past climate signals at that time, and transport of these materials to the depositional site enables χ fd /HIRM to record contemporary climate in the source regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4m). Central Asian aridification has also been dated to 3.3 Ma, based on halite content, grain size, and magnetic proxies from the Qaidam Basin 52 . All of these developments would have impacted atmospheric dynamics and latitudinal temperature gradients that drive seasonal North African climate variability; we therefore retain H2 as a possibility.…”
Section: African Climate/environment Shift At 32 Mamentioning
confidence: 99%